Characteristics of SARS-CoV-2 infection in pregnant and puerperal women at Callao national hospital, Peru - Zumalave Grados, Isabel (2020)
Introduction: It is known that pregnant women are more susceptible to respiratory infections, but the behavior of the SARS-CoV-2 infection is yet to be known. Objective: To describe the epidemiological characteristics of pregnant and puerperal women infected with SARS-CoV-2 at Hospital Nacional Daniel Alcides Carrión, Callao, Peru. Methods: Descriptive cross-sectional study. All pregnant women hospitalized between May 1 and July 31, 2020 with diagnosis of SARS-CoV-2 infection by either the rapid serological test or the RT-PCR test were selected. Results: During the study period, 671 patients were screened; 308 pregnant women and 9 puerperal women were diagnosed with SARS-CoV-2 infection. The most common symptoms were cough (57%) and dyspnea (35%). 95% were asymptomatic, 2% presented mild disease, 1% moderate, and less than 1% severe disease. Only one maternal death was registered. 69% of deliveries were vaginal and 31% were delivered by cesarean section. Conclusions: The behavior of SARS-CoV-2 infection in the pregnant women studied did not differ from that found in the general population of the same age.